Os efeitos de curto e longo prazo dos videogames violentos na agressão - Mariano, Tailson Evangelista (2020)
The study of the effects of video games on aggression was developed in the last 30 years. However, little is known about the effect of violent video games on attitudes towards firearms and the intention to own a firearm. Thus, the present thesis aimed to overcome this gap by analyzing the relationship between playing violent video games and attitudes, and aggressive behavior. To this end, it proposes the hypothesis that exposure to violent video games is positively correlated with these variables To test this hypothesis, two cross sectional studies were conducted with young adolescents N 479, M age 15.7) and adults N 320, M age 22.0) and one experimental study N 66, M age 23.6). Taken together, cross sectional studies showed that a) there is a positive correlation between playing violent video games and physical aggression in youth and adults b) and a positive correlation with favorable attitudes and the intention to own a firearm It also showed that the participants' sex, how long they have been playing violent video games and hours of play per week act as predictors of the intention to own a firearm (long term effect). The experimental study showed that playing violent video games for 20 minutes influences aggressive behaviors (short term e ffect). These results confirm the hypotheses raised and converge with those found in other research, confirming a theoretical hypothesis of the General Aggression Model that exposure in violent media can increase or affect aggressive behavior.